Peranan Koperasi Baruna sebagai Lembaga Ekonomi Pengembangan Pesisir (LEPP) dalam Peningkatan Kesejahteraan Nelayan di Kawasan Minapolitan Pengambengan, Jembran - Anggreni, Ketut; Suparta, Nyoman Suparta; Sri Astiti, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 3 No 1 (2015): Vol. 3 - No. 1 - Mei 2015, 2015)
Cooperative LEPP Baruna is a container of economic activity for fishermen to improve  the welfare of its members. The role of cooperatives providing services and goods for the fishermen. The purpose of this study to determine (1) the role of cooperatives LEPP Baruna in the provision of services and goods, (2) the level of welfare of fishersmen in the Minapolitan area, (3) the relationship between the role of cooperative to the fishermen’s welfare level, and (4) the differences welfare between fishermen  who borrowed capital to who did not. The respondents of this study were 90 people which were determined by  random sampling. The type of data arequalitative and quantitative. The method of data  collection are : (1) structured in-depth interviews using questioner, (2) documentation, and (3) observation. Methods of descriptive data analysis and partialleast square analysis. The results of study showed that, the role of cooperatives for the provision of services and goods including high category, the level of welfare of fishermen in Minapolitan Pengambengan include high category (score of 3.83). The welfare using seven indicators such as : food, clothing, shelter, health, education, arts/recreation, and religious/spiritual. The relationship between LEPP Baruna cooperative role in the provision of services and goods to the welfare of fishermen in Minapolitan proven having positive influence and significant (t-statistic> 1.654). Whereas, in the provision of goods gave real positive effect to the welfare of fishermen. The average of respondents’s income  who borrowed capital was Rp. 1,962,161.29 and who didn’t was Rp. 1.866.250,00. Based on the t-test is known that the average income was not significant. It can be suggested that the role of cooperative LEPP  Baruna in the provision of goods and services can be improved, provide cheap staple for fishermen also. In the other side, the cooperative LEPP Baruna can provide fuel for the fishing operational.
Keywords: the role, cooperative LEPP Baruna, telfare, minapolitan